2011
DOI: 10.1375/twin.14.6.539
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral-Genetic Study of Alexithymia and its Relationships with Trait Emotional Intelligence

Abstract: The present study is the first to examine relationships between alexithymia and trait emotional intelligence (trait EI or trait emotional self-efficacy) at the phenotypic, genetic, and environmental levels. The study was also conducted to resolve inconsistencies in previous twin studies that have provided estimates of the extent to which genetic and environmental factors contribute to individual differences in alexithymia. Participants were 216 monozygotic and 45 dizygotic same-sex twin pairs who completed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
2
14
1
Order By: Relevance
“…These results provide a valuable replication of Baughman et al's (2011) small-sample pilot study, in which similar results were reported. The findings allow us to conclude that, although alexithymia and trait EI are distinct, they do also share common attributes.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These results provide a valuable replication of Baughman et al's (2011) small-sample pilot study, in which similar results were reported. The findings allow us to conclude that, although alexithymia and trait EI are distinct, they do also share common attributes.…”
Section: Discussionsupporting
confidence: 81%
“…Two recent BG studies reported similar results (Baughman et al, 2011;Picardi et al, 2011). Baughman et al (2011) further reported that the phenotypic correlations that they observed between alexithymia and trait EI were attributable to correlated genetic and correlated non-shared environmental factors.…”
Section: Behavior Genetic Studies Of Alexithymiamentioning
confidence: 55%
See 3 more Smart Citations